Assessing patterns in introduction pathways of alien species by linking major invasion data bases. Issue 2 (21st November 2016) - Saul, Wolf‐Christian; Roy, Helen E.; Booy, Olaf; Carnevali, Lucilla; Chen, Hsuan‐Ju; Genovesi, Piero; Harrower, Colin A.; Hulme, Philip E.; Pagad, Shyama; Pergl, Jan; Jeschke, Jonathan M.
Summary: Preventing the arrival of invasive alien species (IAS) is a major priority in managing biological invasions. However, information on introduction pathways is currently scattered across many data bases that often use different categorisations to describe similar pathways. This hampers the identification and prioritisation of pathways to meet the main targets of recent environmental policies. Therefore, we integrate pathway information from two major IAS data bases, IUCN's Global Invasive Species Database (GISD) and the DAISIE European Invasive Alien Species Gateway, applying the new standard categorisation scheme recently adopted by the Convention on Biological Diversity (CBD). We describe the process of mapping pathways from the individual data bases to the CBD scheme and provide, for the first time, detailed descriptions of the standard pathway categories. The combined data set includes pathway information for 8323 species across major taxonomic groups (plants, vertebrates, invertebrates, algae, fungi, other) and environments (terrestrial, freshwater, marine). We analyse the data for major patterns in the introduction pathways, highlighting that the specific research question and context determines whether the combined or an individual data set is the better information source for such analyses. While the combined data set provides an improved basis for direction‐setting in invasion management policies on the global level, individual data sets often better reflect regional idiosyncrasies. The combined data set should thus be considered in addition to, rather than replacing, existing individual data sets. Pathway patterns derived from the combined and individual data sets show that the intentional pathways 'Escape' and 'Release' are most important for plants and vertebrates, while for invertebrates, algae, fungi and micro‐organisms unintentional transport pathways prevail. Differences in pathway proportions among marine, freshwater and terrestrial environments are much less pronounced. The results also show that IAS with highest impacts in Europe are on average associated with a greater number of pathways than other alien species and are more frequently introduced both intentionally and unintentionally. Synthesis and applications . Linking data bases on invasive alien species by harmonising and consolidating their pathway information is essential to turn dispersed data into useful knowledge. The standard pathway categorisation scheme recently adopted by the Convention on Biological Diversity may be crucial to facilitate this process. Our study demonstrates the value of integrating major invasion data bases to help managers and policymakers reach robust conclusions about patterns in introduction pathways and thus aid effective prevention and prioritisation in invasion management.